Nozioni di base della lingua italiana per i lavoratori del turismo I - Kompara, Mojca (University of Maribor Press, 2019)
La monografia professionale Nozioni di base della lingua italiana per il settore del turismo rappresenta una base eccellente per tutti coloro che operano nel campo del turismo e usano la lingua italiana. La monografia comprende 23 unità, che offrono al lettore sia nozioni teoriche sia l’applicazione delle stesse nel linguaggio settoriale del turismo. Il lettore ha la possibilità di arricchire il proprio vocabolario settoriale del turismo grazie ai testi autentici di vari settori come quello alberghiero, la ristorazione, le destinazioni turistiche, la gastronomia e la vinificazione. Ciononostante, gli argomenti discussi non si limitano esclusivamente al settore del turismo, ma includono anche concetti culturali, che racchiudono punti di vista multidisciplinari e multiculturali, fornendo al lettore una visione completa delle basi della lingua italiana nel settore del turismo. Basics of the Italian Language for Tourist Workers I. The professional monograph Osnove italijanskega jezika za turistične delavce I is an excellent foundation for all individuals who work in the field of Italian language in tourism. The work comprehensively covers 23 units in which the author directs the reader from the theoretical starting points, which include the knowledge of sounds, letters, nouns, gender, definite and indefinite articles, adjectives, pronouns and three verbal tenses, namely, present, past and future, to practical concepts that focus on the practical use of the Italian language in tourism with contents that narrowly and broadly cover the professional field of tourism. Terminologically and thematically, the work focuses on basic communication topics that are gradually and in line with the level of difficulty upgraded with topics that are integrated in the tourist context. In the discussed specific topics, the work presents terminology from the fields of hotel management, catering, Italy and Italians, Italian culture and history, tourist destinations, gastronomy and winemaking. The work is enriched with authentic texts from the field of tourism that are adapted to the individual thematic groups and to the difficulty level of the learners. All of the above can be linked to the daily practice of tourism workers in communication and interaction with Italian guests and to all those who encounter tourism in Italy and Slovenia. The work qualitatively rounds up grammatical and terminological aspects from the field of tourism and adds current contents and real texts from the field of tourism. However, the presented topics are not limited just to the field of tourism, but also include a culturally diverse, multidisciplinary and multicultural view. With the monograph, the reader acquires a comprehensive view of the basics of communication with Italian guests in tourism context.